PRESCHOOL EDUCATION STUDENTS’ ATTITUDES ABOUT THE POSSIBLE IMPACT OF MUSIC ON CHILDREN’S SPEECH DEVELOPMENT - Blaženka Bačlija Sušić (International Journal of Cognitive Research in Science, Engineering and Education, 2019)
Music and language are means of human communication, whose common medium is the sound occurring in a unit of time. Numerous relevant studies show that the constant implementation of various forms of musical activities influence the development of a child’s speech and motivates the development of pre-reading skills. A survey formed for the purpose of the study explored the positions of the students of the part-time studies of Early and Pre-school Education on the use of musical, creative musical, and multi-modal activities in their immediate methodical practice, as well as their possible impact on children’s speech development. The results of the study show that the participants believe that the development of a child’s speech is most influenced by musical activities containing multiple verbal elements (children’s singing games, songs and counting rhymes) which are more frequently carried out in practice. Although the participants believe that the activities of rhythmical speech and creating a text to an existing melody influence the development of a child’s speech the most, it is more common in practice to conduct creative musical activities, such as listening to music while dancing and/or painting, as well as those activities related to sound sensitivity, which may be due to the competences of the participants in the listed areas. The respondents who believe that multi-modal activities contribute to the development of a child’s speech, often carry them out more frequently in their methodical practice. The results of the study represent a significant contribution to the further improvement of educational practices.